Nesting success and potential nest predators of the red Junglefowl (Gallus gallus jabouillei) based on camera traps and artificial nest experiments - Rao, Xiaodong; Li, Jialing; He, Binbin; Wang, Hesheng; Wu, Guanmian; Teng, Tiantian; Ling, Qingping (Frontiers in Ecology and Evolution, 2023)
Breeding success is an important factor determining fecundity with nest predation being the main factor limiting avian breeding success. Understanding of nest predation and its influencing factors are highly significant to explore the dynamics of bird populations and developing appropriate conservation strategies. In two breeding seasons of the year 2020 and 2021, natural nests of the red junglefowl (Gallus gallus jabouillei) were systematically searched and monitored using infrared camera, in two nature reserves (Datian and Bangxi) of tropical Hainan island, China. Results showed that breeding season of the red junglefowl is mainly from March to July, with April being the breeding peak. The clutch size was 5.15 ± 1.28 (n=13), and nesting success of natural nests was 31.2%, with nest predation accounting for 45.4% of nest failure. Artificial nest experiments showed that predation rates of artificial nests were 25% (Datian, 2020), 6.67% (Datian, 2021), and 0% (Bangxi, 2020). Rodents, reptiles, and coucals are the main nest predators of red junglefowls, while activities of Hainan Eld's deers (Panolia siamensis) may interfere with the reproduction of red junglefowls. We suggest that the conservation management policies should consider the impacts on junglefowls’ breeding success when reconstructing the suitable habitat of the Hainan Eld's deer.